Broadening energy access for poor households in rural malawi: How pico solar, mobile money, and cloud-based services are being combined to address energy exclusion - Walwyn, David R.; Hanlin, Rebecca (Frontiers in Energy Research, 2022)
Solar lighting has become the primary lighting source for households within rural Malawi, where many households remain off-grid and are unable to afford the purchase of large, independent power systems. However, this success has not been without its challenges. The paradox is that, historically, even the lowest cost systems require an initial investment beyond the means of low-income households, and hence necessitate the use of expensive and exploitative financing options, such as those offered by micro-financial institutions. In this study, we explore in a case-study, how one solar company, Yellow, has overcome this structural inequity by combining three low-cost technologies, namely pay-as-you-go, mobile money (MoMo), and cloud-based services (XaaS), to develop a novel platform, referred to as Ofeefee, which is able to deliver products into a market characterized by a weak retail infrastructure and low purchasing power. The result was better quality lighting at a lower levelized cost than traditional technologies. In so doing, the paper highlights the importance of thinking not just in broad energy access terms but the importance of discriminating between energy and lighting to disaggregate the needs of energy poor communities more appropriately.